Korelasi Kecemasan dan Sport Motivation terhadap Hasil Prestasi Atlet PPLOP Jawa Tengah pada Kejuaraan Nasional Pencak Silat - Khozanah, Lisna Maulidina; Sungkowo; Hadi (MAN Insan Cendekia Jambi, 2025)
The purpose of this study was to determine the correlation of anxiety and sport motivation to the achievement of pencak silat athletes at PPLOP Central Java. The subjects of this study were 13 athletes aged 16-19 years consisting of 8 men and 5 women. This research technique uses quantitative correlation method with data analysis method in the form of Pearson correlation test. The research findings showed a significant inverse relationship between anxiety and athlete achievement (r = -0.644; p = 0.018), which means the more anxious an athlete is, the less able to achieve maximum results. On the other hand, there is a strong positive correlation between sport motivation and achievement results (r = 0.606; p = 0.028). That is, the greater one's influence on sport, the greater the success. These consequences highlight the importance of maintaining psychological elements, especially anxiety control and increasing athletes' sport motivation, with the aim of improving the overall performance of pencak silat athletes. Therefore, psychological techniques and mental training should be an important element in the application of athlete training.